A living bdelloid rotifer from 24,000-year-old Arctic permafrost - Shmakova, Lyubov; Malavin, Stas; Iakovenko, Nataliia; Vishnivetskaya, Tatiana; Shain, Daniel; Plewka, Michael; Rivkina, Elizaveta (Current biology, 2021)
In natural, permanently frozen habitats, some organisms may be preserved for hundreds to tens of thousands of years. For example, stems of Antarctic moss were successfully regrown from an over millennium-old sample covered by ice for about 400 years1. Likewise, whole campion plants were regenerated from seed tissue preserved in relict 32,000-year-old permafrost2, and nematodes were revived from the permafrost of two localities in northeastern Siberia, with source sediments dated over 30,000 years BP3. Bdelloid rotifers, microscopic multicellular animals, are known for their ability to survive extremely low temperatures4. Previous reports suggest survival after six to ten years when frozen between -20° to 0°C4-6. Here, we report the survival of an obligate parthenogenetic bdelloid rotifer, recovered from northeastern Siberian permafrost radiocarbon-dated to ∼24,000 years BP. This constitutes the longest reported case of rotifer survival in a frozen state. We confirmed the finding by identifying rotifer actin gene sequences in a metagenome obtained from the same sample. By morphological and molecular markers, the discovered rotifer belongs to the genus Adineta, and aligns with a contemporary Adineta vaga isolate collected in Belgium. Experiments demonstrated that the ancient rotifer withstands slow cooling and freezing (∼1°C min-1) for at least seven days. We also show that a clonal culture can continuously reproduce in the laboratory by parthenogenesis.
Keywords: Sibiř; metagenom; vířníci; zmrazování; partenogeneze; Permafrost; Metagenome; Animals; permafrost; Siberia; Freezing; zvířata; Rotifera; Parthenogenesis